Nurse Leadership Style in Indonesia Hospitals: A Literature Review - Indiati Indiati; Sigit Wahyudi; Antonius Rino Vanchapo (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Health services are one of the health service providing institutions. One of the service providers is a nurse. However, the nurse's work performance is very dependent on one of them is the leadership style of the head of the room. The purpose of this study was to look at the leadership style of nurses in Indonesia. The research method used in this study is Literature Review with Prism Method. The keywords used are PICO. P: Hospital Nurse in Indonesia. I: Leadership style (transformational, transactional, liberal, democratic, autocratic), C: -, O: Work performance, motivation, job satisfaction. In addition, researchers also made inclusion criteria in article screening, namely: available in full text, in Indonesian, where the research was carried out in the Hospital, research year 2012-2022. The data base used is Google Scholar. Screening the title of the same article, as well as the last 10 years of research, is not an article but a book of 8938 articles. Furthermore, eligibility does not meet the inclusion criteria of 881. Leadership styles have their own disadvantages and advantages. A good leadership style is determined by the situation and the conditions of the work environment.